Total factor productivity (TFP) within Malaysian companies / Prof. Dr. Suzana Sulaiman, Prof. Dr. Normah Omar and Prof. Dr. Ibrahim Kamal Abdul Rahman - Sulaiman, Suzana; Omar, Normah; Abdul Rahman, Ibrahim Kamal (2010)
Total Factor Productivity (TFP) refers to the efficiency in using existing resources. It includes all the qualitative factors that enable existing resources to be used effectively and efficiently. The determinants of the TFP growth are education and training, capital structure, demand intensity, economic restructuring and technical progress. Since the IMP2 Malaysia had shifted its strategy from input-driven growth to productivity-driven growth. There is a variety of factors which affect productivity, both positively and negatively, highly and marginally controllable at the company level and controllable only at the national level. The objective of this study is to explore and analyse the relationship between the input (fixed assets) and TFP growth. Through efficient usage of inputs, more output can be produced thus enabling the firm to achieve higher sales, lower costs and eventually higher profit. This study was conducted on a sample of 500 Malaysian main board companies. The findings showed that only 229 companies (45.8%) show an increase in their fixed assets in year 2002 to 2003.